Immune response of broiler chickens immunized orally with the recombinant proteins flagellin and the subunit B of cholera toxin associated with Lactobacillus spp. - Baptista, A. A. S. [UNESP]; Donato, T. C. [UNESP]; Garcia, K. C. O. D. [UNESP]; Goncalves, G. A. M. [UNESP]; Coppola, M. P. [UNESP]; Okamoto, Adriano Sakai [UNESP]; Sequeira, Julio Lopes [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Oxford University Press, 2014)
This study investigated the immune response of broiler chickens with oral treatment of a Lactobacillus spp. pool (PL) associated with microencapsulated recombinant proteins flagellin (FliC) and the subunit B of cholera toxin (CTB). Immune responses were evaluated by measuring IgA from intestinal fluid, serum IgY, and immunostaining of CD8(+) T lymphocytes present in the cecum. The evaluations were performed on d 0, 7, 14, 21, and 28 posttreatment. A significant increase (P < 0.05) was observed in IgA levels in all immunized groups, especially 3 wk after immunization. Treatments 2 (recombinant CTB) and 3 (recombinant FliC+CTB) showed the highest concentrations. Similarly, serum concentrations IgY (mu g/mL) increased along the experiment, and the means for treatments 2 and 3 showed significant differences (P < 0.05) compared with controls, reaching concentrations of 533 and 540 mu g/mL, respectively. The number of CD8+ T lymphocytes in all treatments greatly differed (P < 0.05) compared with the negative control at 21 d posttreatment. However, only treatment 2 (recombinant CTB), 4 (PL), and 5 (recombinant FliC+ recombinant CTB + PL) remained significantly (P < 0.05) different from the control at 28 d posttreatment. Thus, it is concluded that the microencapsulated recombinant proteins administered orally to broiler chickens are capable of stimulating humoral and cellular immune response, and the combinations of these antigens with Lactobacillus spp. can influence the population of CD8+ T cells residing in the cecum.
Keywords: recombinant flagellin; recombinant cholera toxin subunit B; Lactobacillus species; immunoglobulin A; CD8(+) T lymphocyte